Hidden Trends in Modern Sickness Rate Dynamics in Children - Yuri Arkadievich Tyukov (Journal of Global Pharma Technology, 2016)
The health state of children in Russia has a number of unfavorable trends, i.e. chronic diseases increase, and infectious diseases increase. Objective: To obtain an objective characteristic of the overall sick rate in children of the regional center and the role of urgent pathology in its level and dynamics. Methods: The study base was ‘Children's City Clinical Hospital #8’, serving the entire child population of the Metallurgical District, Chelyabinsk. The number of children for the period from 2008 to 2017 raised from 23.4 thousand to 26.5 thousand children. Results: The total disease appealability decreased from 2195.0 per 1,000 children to 1,733.2 in 2017. At the same time, the total urgent morbidity, according to the emergency department, ambulance and hospital wards increased to 1,025.3 cases per 1 000 children Conclusion: A disease appeal ability decrease is counterbalanced by an increase in urgent morbidity, which means the absence of a real improvement in children's health indicators.Keywords: Sick rate, Child population, Urgent morbidity, Disease appeal ability, State of health.